The expressions of Ret/PTC and p53 in normal, benign and malignant thyroid lesions - Omar, Effat; Madhavan, M.; Othman, Nor Hayati (Pusat Pengajian Sains Perubatan, Universiti Sains Malaysia, 2005)
Goiter is a highly prevalent problem in the local population. Studies at HUSM have found high percentage of papillary carcinoma within this lesion. Ret/PTC is a recently discovered oncogene which is solely related to papillary carcinoma. It has been proven to play a major role in the pathogenesis of this malignant lesion. P53 gene is a well known tumour suppressor gene, usually associated with the undifferentiated thyroid carcinoma. Immunohistochemistry is able to demonstrate p53 mutation in well differentiated thyroid carcinoma. This study aims to investigate the expression of ret and p53 in the local normal, benign and malignant thyroid lesions in order to shed light on the pathogenesis of papillary carcinoma and explain the high prevalence of this condition among the nodular hyperplasia ( multinodular goiter) cases. From the records of HUSM pathology department, archival blocks from 50 follicular adenomas, 66 nodular hyperplasia cases and 53 papillary carcinoma cases were retrieved. They were studied by immunohistochemistry method for the presence of ret/PTC and p53 mutant protein within the follicular cells. Normal thyroid tissues from 74 of the cases were utilized as controls. Ret/PTC is expressed by 5.4% of normal thyroid tissue, 18% of follicular adenomas, 22.7% of nodular hyperplasia cases and 71.7% of papillary carcinomas. There is no statistically significant difference of ret expression between pure nodular hyperplasia and the ones with coexisting papillary carcinoma.